1997
DOI: 10.1159/000119375
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Topographical EEG Features with Clinical Severity in Mild and Moderate Dementia of Alzheimer Type

Abstract: Quantitative electroencephalography (qEEG) and the Folstein Mini Mental State examination (MMSE) were obtained from 31 patients affected by probable dementia of Alzheimer’s type (DAT). qEEG data were examined both by spectral analysis (Fast Fourier Transformation) and by single frequency band topographical centroid, and compared with those of 24 healthy subjects of the same age group. DAT patients were found to have higher absolute power in the slow (delta and theta) frequency bands. Quantitative topographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 29 publications
9
45
0
Order By: Relevance
“…In the present casuistic, the finding of an increase in the theta power and to a lesser degree in the delta band in the AD group is in agreement with the literature 4,21 . In this survey the alterations in coherence were limited to the alpha and beta bands and the frontal and temporal regions (F3-F4 and F7-F8), similarly to that described in the literature [5][6][7] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present casuistic, the finding of an increase in the theta power and to a lesser degree in the delta band in the AD group is in agreement with the literature 4,21 . In this survey the alterations in coherence were limited to the alpha and beta bands and the frontal and temporal regions (F3-F4 and F7-F8), similarly to that described in the literature [5][6][7] .…”
Section: Discussionsupporting
confidence: 93%
“…With respect to MMSE, elevated negative correlation between delta and theta activities and the MMSE score was reported for patients with dementia 9 , whereas in other studies they were not found 21 . On analyzing together normal elderly subjects and those with cognitive compromise, Onishi et al 12 found a significant regression model to forecast the MMSE score using theta and alpha 1 powers.…”
Section: Relationships Between Absolute Power and Cognitive Aspectsmentioning
confidence: 77%
“…The following standard band frequencies were studied: delta (2 -4 Hz), theta (4 -8 Hz), alpha 1 (8 -10.5 Hz), alpha 2 (10.5 -13 Hz), beta 1 (13 -20 Hz), and beta 2 (20 -30 Hz). These band frequencies were chosen averaging those used in previous relevant EEG studies on dementia in order to render comparable present results with them (Leuchter et al, 1993;Jelic et al, 1996; Besthorn et al, 1997; Chiaramonti et al, 1997;Rodriguez et al, 1999aRodriguez et al, , 1999b and with previous findings of our Consortium (Babiloni et al, , 2005b. This advantage was supposed to compensate the use of odd 10.5 Hz as half-limit between alpha 1 and alpha 2 bands.…”
Section: Spectral Analysis Of the Eeg Datamentioning
confidence: 84%
“…This type of analysis includes the estimation of the power density of selected EEG frequency bands (AD; Besthorn et al, 1997;Chiaramonti et al, 1997;Schreiter-Gasser et al, 1994). Compared to normal subjects, Alzheimer's disease (AD) patients are known to have 'slowing of the EEG,' namely through increase of the delta (0.5 -4 Hz) and theta (4 -8 Hz) power, along with decrease of the alpha power (8 -13 Hz).…”
Section: Introductionmentioning
confidence: 99%